2005
DOI: 10.1021/ja050612p
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular and Intramolecular, Platinum-Catalyzed, Acceptorless Dehydrogenative Coupling of Hydrosilanes with Aryl and Aliphatic Methyl C−H Bonds

Abstract: Intermolecular acceptorless dehydrogenative coupling of silanes with arene C-H bonds and intramolecular coupling of silanes with aryl and alkyl C-H bonds occur in good yield in the presence of 5 mol % of TpMe2PtMe2H (TpMe2 = hydridotris(3,5-dimethylpyrazolyl)borate) and related platinum(IV) complexes. The intermolecular reactions of arenes occurred with both trialkyl and dialkylaryl silanes. Intramolecular reactions of dialkylsilylalkylarenes occurred at aryl C-H bonds, and reactions of tributylsilane or dibut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
86
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(94 citation statements)
references
References 30 publications
2
86
0
5
Order By: Relevance
“…Furthermore, reactions in toluene and mesitylene (vide infra) do give solvent-derived silylated products and in the case of toluene where aromatic regioisomers arise, benzylic C-H silylation prevails. 16 Such reactivity with unactivated substrates is particularly remarkable since transition metals and directing groups 17 or very high temperatures 18 are normally required for related functionalizations. While this transition-metal-free C-H silylation process has potential applications in organic synthesis 19 and is itself poised for further investigation, we rst focused on tuning the selectivity to favour the intended C-O scission.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, reactions in toluene and mesitylene (vide infra) do give solvent-derived silylated products and in the case of toluene where aromatic regioisomers arise, benzylic C-H silylation prevails. 16 Such reactivity with unactivated substrates is particularly remarkable since transition metals and directing groups 17 or very high temperatures 18 are normally required for related functionalizations. While this transition-metal-free C-H silylation process has potential applications in organic synthesis 19 and is itself poised for further investigation, we rst focused on tuning the selectivity to favour the intended C-O scission.…”
Section: Resultsmentioning
confidence: 99%
“…However, in contrast to many reports on the cleavage of the C(sp 3 ) À Si bonds through stoichiometric reactions [8,9] or through transition-metal-catalyzed reactions of activated C(sp 3 ) À Si bonds, [3c, 4b-d, 10] little is known about the transitionmetal-catalyzed cleavage of unactivated C(sp 3 )ÀSi bonds. [11][12][13][14][15] Rauf and Brown reported the cleavage of a C(sp 3 )ÀSi bond in an SiMe 3 group by using the SiMe 3 group as a methyl source in a Pd-catalyzed oxidative methylation of olefins.…”
mentioning
confidence: 94%
“…6,7 While the intramolecular CH silylation of other substrates has also been investigated, 6 to our knowledge, the platinumcatalyzed dehydrogenative cyclization of 2-(dialkylsilyl)biaryls 1 has not been reported. Therefore, we decided to investigate the platinum-catalyzed intramolecular CH silylation of 1.…”
Section: Abstract: C-h Activation | Platinum Catalyst | C-si Bond Formentioning
confidence: 99%
“…5 For example, the Hartwig group, as well as our own group, have demonstrated that platinum complexes bearing the hydrotris(3,5-dimethylpyrazolyl)borate (Tp Me2 ) ligand showed high catalytic activities in dehydrogenative aromatic CH silylation with hydrosilanes. 6,7 While the intramolecular CH silylation of other substrates has also been investigated, 6 to our knowledge, the platinumcatalyzed dehydrogenative cyclization of 2-(dialkylsilyl)biaryls 1 has not been reported. Therefore, we decided to investigate the platinum-catalyzed intramolecular CH silylation of 1.…”
mentioning
confidence: 99%